2016
DOI: 10.1136/bmjspcare-2015-000921
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and patients with palliative cancer

Abstract: Vitamin D is a hormone that is synthesised in the skin in the presence of sunlight. Sufficient vitamin D levels are important-not only for a healthy skeleton-but also for a healthy immune system. Many patients with cancer have insufficient vitamin D levels, and low vitamin D levels are associated with increased 'all-cause mortality' and especially mortality due to cancer. Low vitamin D levels have also been associated with increased risk of infections, increased pain, depressive disorders and impaired quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
10
0
5
Order By: Relevance
“…Vitamin D status is important for host immunity against various infections [ 16 , 17 , 18 ] and has also been suggested to play a role in the quality of life of palliative cancer patients [ 15 , 19 ]. Thus, we evaluated whether the vitamin D status of the patients was related to antibiotic-use or with response to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D status is important for host immunity against various infections [ 16 , 17 , 18 ] and has also been suggested to play a role in the quality of life of palliative cancer patients [ 15 , 19 ]. Thus, we evaluated whether the vitamin D status of the patients was related to antibiotic-use or with response to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that vitamin D inhibits the synthesis of Prostaglandin E2 (PGE2) [ 3 ]. Both observational and interventional studies suggest a role for vitamin D in pain intensity and in management of pain in varying clinical settings [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Despite these data, three meta-analyses of randomized and placebo-controlled trials (RCTs) could not establish a correlation between vitamin D supplementation and pain reduction [ 8 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several welldocumented risk factors for psychological distress, including younger age, a history of psychiatric illness, poor social support, advanced cancer, functional impairment, and uncontrolled pain [4]. Additionally, biological factors, such as activation of the hypothalamic–pituitary–adrenal axis or low vitamin D levels, are associated with psychological distress [5,6], and genetic components, such as the serotonin transporter (5-HTT) and brainderived neurotrophic factor (BDNF) genes, are responsible for vulnerability to depression in cancer patients [7].…”
Section: Introductionmentioning
confidence: 99%